Peran Perpustakaan sebagai Tempat Rekreasi di Perpustakaan RSUD Tengku Rafi’an - Nasrullah; Aprilia, Khoirunnisa; Tawakkal; Fauzan (Literatify: Trends in Library Developments, 2026)
The purpose of this study was to determine the role of the library as a place of recreation in the hospital and what are the driving and inhibiting factors in the library. This study uses a qualitative descriptive research method. Informants in this study were selected based on individual considerations who understand the background of the establishment of the library and users who have used the library facilities at the Tengku Rafi'an Regional General Hospital. Data collection for this study was carried out by means of observation, interviews, and documentation. The results of this study are that the Tengku Rafian Regional General Hospital library provides a role such as providing several services including circulation services, child services, and the internet. And there are several driving and inhibiting factors, such as the driving factor of having a modern library building and having a reading park. While the inhibiting factors are that many people still do not know about the existence of the library, the lack of library collections and the absence of a fixed budget.